Methylation of SOCS-3 and SOCS-1 in the carcinogenesis of Barrett's adenocarcinoma. Issue 8 (21st March 2007) - Tischoff, I; Hengge, U R; Vieth, M; Ell, C; Stolte, M; Weber, A; Schmidt, W E; Tannapfel, A
Abstract : Background: The suppressors of cytokine signalling (SOCS) are inhibitors of cytokine signalling; methylation of SOCS-3 has been implicated in the tumorigenesis of liver as well as head and neck cancer. Aims: This study was performed to elucidate the role of SOCS-1 and SOCS-3 in Barrett's adenocarcinoma and its precursor lesions. Methods: DNA of specimens from 19 Barrett's adenocarcinomas, 56 Barrett's intraepithelial neoplasias (n = 29 low grade and n = 27 high grade), 30 Barrett's mucosa without neoplasia, 20 samples of normal squamous and gastric epithelium and four cell lines were studied using methylation specific PCR for the SOCS-1 and SOCS-3 promoter following microdissection. The presence of SOCS-3 mRNA transcripts was confirmed by semiquantitative real time PCR, and the SOCS-3 protein was analysed immunohistochemically. Results: In normal squamous epithelium and normal gastric mucosa, neither SOCS-3 nor SOCS-1 methylation was observed. In Barrett's mucosa without intraepithelial neoplasia, SOCS-3 methylation occurred in 4/30 cases (13%) whereas SOCS-1 was unmethylated. A hypermethylated SOCS-3 promoter was found in 14/19 Barrett's adenocarcinomas (74%) and in 20/29 high and 6/27 low grade intraepithelial neoplasias (69% and 22%, respectively). SOCS-1 promoter hypermethylation occurred in 8/19 adenocarcinomas (42%) and in 6/29 high grade and 1/27 low grade intraepithelial neoplasias (21% and 4%, respectively). Methylation of the SOCS-3 promoter correlated with downregulation of SOCS-3 transcripts and protein expression in these tumours and various cell lines. In the cell lines tested, SOCS-3 and SOCS-1 transcripts increased after treatment with the demethylation compound 5-aza-2-deoxycytidine. Conclusions: These data indicate that promoter methylation and subsequent transcript downregulation of SOCS-3 transcripts and, to a much lesser extent, SOCS-1 are involved in the multistep carcinogenesis of Barrett's adenocarcinoma.